Extra pulmonary tuberculosis: health care challenges faced by a rural family in a low middle-income country - Kaur, Rashmeet; Dhiman, Anupama; Navpreet; Parashar, Anupam (International Journal Of Community Medicine And Public Health, 2025)
Tuberculosis (TB) is a highly infectious disease prevalent in many developing countries like India. The variation in its clinical presentation and the social stigma attached to the disease are the mainstay for its delay in diagnosis and management. We report a case of extrapulmonary TB (EPTB) in an individual from a rural family background. Despite a known family history of TB, there were delays in diagnosis at both the primary (patient) and secondary (healthcare) levels. In developing countries like India, the high prevalence of TB should foster clinicians to be highly suspicious even if the patient presents with non-specific symptoms in establishing early diagnosis and treatment of TB to reduce morbidity and mortality.